IMPLEMENTASI PROGRAM KELUARGA BERENCANA DALAM PEMBANGUNAN KELUARGA SEJAHTERA (STUDI DI KEC. TELEN KABUPATEN KUTAI TIMUR, PROPINSI KALIMANTAN TIMUR) - Heny Purwandiyah (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
One of vision of family planning program is shape the quality family 2016 and to create a happiness family environment, then family able to conduct several functions of family. Based on the data year 2002, amount of poverty population in Telen (subdistrict) are 1676. The causes of poverty are low education, every family has many children, low income. Family program was intended to build social welfare.